DNA methylation signatures in peripheral blood strongly predict all-cause mortality - Zhang, Yan; Breitling, Lutz Philipp; Schöttker, Ben; Brenner, Hermann (Nature Communications, 2017)
DNA methylation is modulated by environmental factors and has a role in many complex diseases. Here, the authors find that methylation at specific DNA sites is associated with all-cause mortality, and a methylation-based risk score may be informative for risk assessment and stratification.